Niacinamide Protects Skin Cells from Oxidative Stress Induced by Particulate Matter - Zhen, Ao Xuan; Piao, Mei Jing; Kang, Kyoung Ah; Fernando, Pincha Devage Sameera Madushan; Kang, Hee Kyoung; Koh, Young Sang; Yi, Joo Mi; Hyun, Jin Won (Biomolecules & therapeutics, 2019)
Niacinamide (NIA) is a water-soluble vitamin that is widely used in the treatment of skin diseases. Moreover, NIA displays antioxidant effects and helps repair damaged DNA. Recent studies showed that particulate matter 2.5 (PM ) induced reactive oxygen species (ROS), causing disruption of DNA, lipids, and proteins; mitochondrial depolarization, and apoptosis of skin keratinocytes. Here, we investigated the protective effects of NIA on PM -induced oxidative stress in human HaCaT keratinocytes. We found that NIA could inhibit the ROS generation induced by PM , as well blocked the PM -induced oxidation of molecules, such as lipids, proteins, and DNA. Furthermore, NIA alleviated PM -induced accumulation of cellular Ca , which caused cell membrane depolarization and apoptosis, and reduced the number of apoptotic cells. Collectively, the findings show that NIA can protect keratinocytes from PM -induced oxidative stress and cell damage.